Fine-Resolution Mapping of TF Binding and Chromatin Interactions - Jenia Gutin; Ronen Sadeh; Nitzan Bodenheimer; Daphna Joseph-Strauss; Avital Klein-Brill; Adi Alajem; Oren Ram; Nir Friedman (Cell Reports, 2018)
Summary: Transcription factor (TF) binding to DNA is crucial for transcriptional regulation. There are multiple methods for mapping such binding. These methods balance between input requirements, spatial resolution, and compatibility with high-throughput automation. Here, we describe SLIM-ChIP (short-fragment-enriched, low-input, indexed MNase ChIP), which combines enzymatic fragmentation of chromatin and on-bead indexing to address these desiderata. SLIM-ChIP reproduces a high-resolution binding map of yeast Reb1 comparable with existing methods, yet with less input material and full compatibility with high-throughput procedures. We demonstrate the robustness and flexibility of SLIM-ChIP by probing additional factors in yeast and mouse. Finally, we show that SLIM-ChIP provides information on the chromatin landscape surrounding the bound transcription factor. We identify a class of Reb1 sites where the proximal −1 nucleosome tightly interacts with Reb1 and maintains unidirectional transcription. SLIM-ChIP is an attractive solution for mapping DNA binding proteins and charting the surrounding chromatin occupancy landscape at a single-cell level. : Mapping transcription factors binding to DNA by chromatin immunoprecipitation sequencing is a key step in studying transcriptional programs. Gutin et al. introduce SLIM-ChIP, a simple, automation compatible protocol, that provides insights about the chromatin landscape at the bound sites. Using this protocol, they discover promoter architectures that enforce unidirectional transcription. Keywords: Reb1, CTCF, ChIP-seq, chromatin, transcription factor, DNA-binding, promoter directionality, nucleosomes